Design and Build Automatic Fan Control Based Internet of Things - Septian, Refli; Achmad Fauzi; Milli Alfhi Syari (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
This research aims to create and develop an automatic fan control system based on the Internet of Things (IoT) that can regulate the room temperature well. The NodeMCU ESP8266 serve as a microcontroller for this system. The DHT22 sensor detects temperature, the L298N Driver Motor controls the speed of the 12V DC fan, and the 16x2 LCD displays temperature information in realtime. When the room temperature exceeds the threshold, the fan will automatically turn on and off when the temperature returns to normal. The Blynk app also allows users to monitor and control fans through smartphones. It allows users to manually control the fan and monitor it remotely. The results of the study show that this system works well and improves user comfort by managing the room temperature. The system also offers high flexibility with IoT integration, allowing for further development for wider applications in home automation and energy management.